Sharia Banking Disputes Settlement: Analysis of Religious Court Decisions in Indonesia - Hidayah, Nur; Azis, Abdul; Mutiara, Tira; Larasati, Diah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This study aims to analyze Sharia banking dispute settlements in Religious Courts regarding Sharia compliance and state regulations. The data is collected from the Supreme Court of the Republic of Indonesia website on Profit Sharing (PLS) financing, musyarakah, and non-profit Sharing (non-PLS) financing, murabahah. It is legal empirical research with a comparative approach. The results of this study indicate that Sharia banking disputes occur partly because there are still legal loopholes due to the general nature of the existing rules leading to multiple interpretations. The disputes are contributed mainly by default and unlawful acts. There are differences in the judge's decisions in the two case studies related to the fulfillment of legal principles in the form of benefits, justice, and legal certainty in the decisions made. Regarding the suitability of the contract, in the murabahah case, the pillars and conditions have been fulfilled, but there are other things that damage the contract. There has been an urgent need to strengthen regulations related to more detailed financing contracts. The regulators should promote an Islamic banking regulatory framework that guarantees legal certainty for both parties, the customers and Islamic financial institutions, as well as provide a stronger legal basis for dispute settlements.